Model Ontologi Personalisasi Konten Mata Kuliah berbasis Gaya Belajar Felder Silverman - Bernard R. Suteja (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Abstract – Personalization using learning style is a personal learning that adapts to any strengths, needs and interests of students. Felder Silverman learning styles used in ontology-based knowledge representation to determine the content of the courses. Finally a student acquire content appropriate course of his learning style.Keywords – Ontology, Felder Silverman, Learning Style